Ovarian hyperstimulation syndrome with carotid artery dissection and cerebral infarction: a case report - Tianhua Fan; Liansheng Ma (BMC, 2023)
Abstract Background and purpose Ovarian hyperstimulation syndrome (OHSS) is one of the most serious iatrogenic complications in assisted reproductive technology, which seem rarely associated with cerebrovascular diseases. We reported a patient diagnosed with OHSS combined with carotid artery dissection and massive cerebral infarction. Case presentation We reported a unique case of a 31-year-old woman who experienced abdominal pain, blurred consciousness, and speech inability after 15-day continuous injection of human gonadotropin for infertility. Imaging examination showed hyperacute cerebral infarction in the left frontotemporal island parietal lobe and left internal carotid artery dissection. After therapeutic use of low-molecular-weight heparin calcium anticoagulation and other conventional cerebrovascular treatments, she eventually achieved a good prognosis. Conclusions OHSS seemd rarely associated with cerebrovascular diseases, such as infarction and carotid artery dissection. Encountering abdominal symptoms combined with neurologic symptoms, a detailed history and a thorough examination are essential. It is necessary to comprehensively analyze the pathogenesis and formulate individualized therapy according to the specific conditions of patients.